PERAN GURU PAI DALAM MEMBENTUKAN KARAKTER KEDISIPLINAN SISWA MASA PANDEMI COVID-19 MELALUI KEGIATAN KEAGAMAAN DI SMP NEGERI 1 KEPANJEN - Tasya Nur Ainiya; Mohammad Afifulloh; Qurroti A’yun (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The character of student’s discipline is increasingly shifting, especially during the pandemic. This is concern for Islamic Religious Education teachers at SMP Negeri 1 Kepanejn, especially student’s discipline in worship. The focus of the researches discusses the level of student discipline, the role of Islamic Religious Education teachers in developing student’s discipline characters, and supporting and habiting factors in forming student discipline characters during the pandemic through religious activities. To achive this goal, the researcher used a phenomenological appoarch with a qualitative research type. Researchers found the result of thi study include the level of student discipline character during the pandemic slightly decreased compared to before the pandemic. The role of the Islamic Religious Education teacher as an initiator by making recap of worship books in order to control the character of student’s discipline. For the supporting factor, namely the awareness in student’s of importance of discipline behavior and good cooperation between parents and teachers. While the inhibiting factors are the lack of parental attention, lack of student awareness, and the existence of environmental factors that prevent student from being disicipline.Kata Kunci: The role of Islamic Religious Education teachers, Discipline Character, Religious Activity.